Stability of nonlinear delayed impulsive control systems via step-function method - Wang, Yinuo; Li, Chuandong; Wu, Hongjuan; Deng, Hao (Chaos, solitons and fractals, 2024)
In this paper, considering that the limited speed of information transfer may generate time delay, which can sometimes influence the stability of the system, but in reality time delay is pervasive, and sometimes can have a positive impact on system’s stability, so it is essential to think about its existence. The nonlinear systems under delayed impulsive control (IC) are investigated here, and we mainly utilize the multiple-spans step-function method to analyse the stability conditions of the considered systems, which can be counted as a generalization of the Lyapunov-like stability method and is less conservative compared with the existing traditional Lyapunov-like function method. Moreover, it is the first time that this method employed for the stability of systems with IC and time delay. Two examples of equidistant impulses of nonlinear autonomous system and non-equidistant impulses of linear time-varying system by using two-spans step-function method are presented to validate the utility of the presented approach, respectively. Besides, the Zeno behavior of autonomous system without time delay is provided and treated by the presented method, which can better manifest the extensive viability of the method compared with the Lyapunov-like function method. •Nonlinear system subject to impulsive control with delay is considered.•Globally uniformly attractive stability is acquired via step-function method.•Relationship between change during flow, decreasing during jump and delay is set up.•Step-function method is firstly used for nonlinear system under impulsive control with delay.